The Dynamics and Legislative Mechanisms of the Collectivisation of Agriculture in Romania. Case Study: The Evolution of the Process of Collectivization in the Former Administrative Region of Cluj (1949-1962) - Borsa, Sanda (Richtmann Publishing, 2012)
Carried out after the model offered by the Soviet Union, the collectivization of agriculture in Romania has been achievedbetween 1949-1962. The subordination of the rural world by the Communist regime, through the collectivization of agriculture, wasachieved, on the one hand, by abolishing private ownership of land and the establishment of cooperative agricultural units (CollectiveAgricultural Farms, Agricultural Associations of Peasants, Agricultural Production Cooperative) and on the other hand, through a seriesof abuses of those responsible for collectivization (quotas, taxes, threats, intimidation, expulsion of children from school if their parentsdid not agree to join the collective farm household or firing the parents for the same reason). The collectivization of agriculture in Clujregion has experienced three distinct phases: 1949-1952 – the emergence of the first Collective Agricultural Farms and AgriculturalAssociations of Peasants; 1953-1958 - the period characterized by a slowdown in the process of collectivization and 1959-1962 - periodcharacterized by an intensification of the collectivization of agriculture, process perceptible through the number of families placed inthese units and also through the many Agricultural Associations of Peasants transformed or merged into Collective Agricultural Farms.This process of intensification of the collectivization is also visible through the merge of various Collective Agricultural Farms in order tofacilitate the establishment of larger agricultural units.